Synthesis and phase transition characterization by polarized optical microscopy and differential scanning calorimetry in hydrogen bonded chiral liquid crystal series:M*SA:nOBAs. (13th June 2018) - Surekha, M.; Ashok Kumar, A.V.N.; Chalapathy, P.V.; Muniprasad, M.; Potukuchi, D.M.
Abstract: Synthesis of hydrogen bonded (HB) liquid crystal dimers, viz., nOBA:M*SA:nOBAs are reported by the soft covalent interaction of chiral 1-Methyl Succinic acid (M*SA) and n-p-n-Alkoxy benzoic acids (nOBAs) with varied (for n = 3, 4, 5, 6, 7, 8, 9, 10, 11 and 12) flexible chain length. M*SA is targeted to act as spacer between nOBA moieties. Polarized Optical Microscopy (POM) and Differential Scanning Calorimetry (DSC) techniques are used to characterize LC phases and transitions. 1H-NMR, 13C-NMR and IR study confirmed the formation of HBFLC dimers. Nematic phase is exhibited by intermediate and higher members for n ≥ 5. SmC* phase is exhibited by higher members for n > 9. Higher order LC phase variances, viz., pentavariant, GFC*AN phase abundance by n = 10 (in heating); and tetravariant, AC*FG phase abundance (in cooling) by n = 12 in higher homologues. AC* transition exhibits weak firs order nature. Phase diagram reveals the presence of INC* multicritical point for n = 9 and AC* tricritical point for n > 12. Influence of flexibility (n), hydrogen bonding interaction, chiral centre on spacer moiety of dimer are discussed in the wake of data reported on nOBAs, structurally similar G*A:nOBAs and other ferroelectric hydrogen bonded LCs.